Sidastrum paniculatum (L.) Fryxell (Malvaceae): A Promising Source of Bioactive Sulfated Flavonoids Against Aedes aegypti L - Marques, Sany D. G.; Fernandes, Diégina A.; Teles, Yanna C. F.; Menezes, Renata. P. B.; Maia, Mayara S.; Scotti, Marcus T.; Agra, Maria F.; Silva, Tania M. S.; de Souza, Maria de Fátima Vanderlei (Frontiers in Pharmacology, 2022)
Aedes aegypti L. is known as the most relevant vector mosquito for viruses such as yellow fever, chikungunya, dengue, and Zika, especially in places with unplanned urbanization and erratic water supply. Plants used in folk medicine have become a useful source of active compounds with the potential to control the dissemination of Ae. aegypti. Compounds isolated from Malvaceae sensu lato have been previously reported as larvicides, repellents and insecticides. Recent studies have demonstrated the anti Ae. aegypti activity of sulfated flavonoids, an uncommon type of flavonoid derivatives. This research reports the phytochemical investigation of Sidastrum paniculatum (L.) Fryxell, a Malvaceae species with the potential against Ae. aegypti. Chromatographic procedures resulted in the isolation of the compounds: stearic acid (1), N-trans-feruloyltyramine (2), acacetin (3), apigenin (4), tiliroside (5), along with the sulfated flavonoids: wissadulin (6), 7,4’-di-O-methyl-8-O-sulfate flavone (7), yannin (8), beltraonin (9a), 7-O-sulfate isoscutellarein (paniculatumin) (9b) and condadin (10). This is the first report of compound 7-O-sulfate isoscutellarein (9b). The structures were elucidated by spectroscopic analysis (NMR, LC-HRMS and FT-IR). The sulfated flavonoids identified were submitted to a ligand-based and structure-based virtual screening against two targets: 1YIY (from adult Ae. aegypti) and 1PZ4 (from Ae. aegypti larvae). The results indicated that when the O-sulfate group is bearing the position 7, the structures are potentially active in 1PZ4 protein. On the other hand, flavonoids with the O-sulfate group bearing position 8 were showed to be more likely to bind to the 1YIY protein. Our findings indicated that S. paniculatum is a promising source of sulfated flavonoids with potential against Ae. aegypti.